Jus Cogens Norms in Dialogue with Norberto Bobbio. Justice, Validity, Effectiveness, and Other Criteria of Analysis - Rosales Zamora, Pablo (2025)
The purpose of this paper is to analyze the norms of jus cogens through the lenses of justice, validity, and efficacy, as proposed by Norberto Bobbio from the perspective of the general theory of law. For this analysis, the «Draft Conclusions on the Identification and Legal Consequences of Peremptory Norms of General International Law (Jus Cogens)» (2022) and the doctrine on jus cogens are reviewed. Furthermore, two additional criteria not addressed by Bobbio are proposed: the political factor and efficiency, aimed at analyzing peremptory norms of general international law.